The accuracy of linear measurements in cone beam computed tomography for assessing intrabony and furcation defects: A systematic review and meta-analysis. - Nurul Ain Mohamed Yusof; Erni Noor; Mohd Yusmiaidil Putera Mohd Yusof (Universidad de Concepción., 2019)
Objective: This study aims to assess the accuracy of the linear measurements of intrabony and/or furcation defect quantified by cone beam computed tomography (CBCT). Material and Methods: A systematic search of the literature was conducted by two authors independently from the PubMed, Scopus, and EBSCO for full articles published in journals between January 2003 and March 2017. Eligible studies were assessed for quality and heterogeneity using the QUADAS-2 tool. A meta-analysis was performed to identify the accuracy of CBCT in the measurement of intrabony defects. The effect size was estimated and reported as the standardised mean difference (SMD). Results: A total of 105 titles and abstracts were screened. Of those, 11 articles met the inclusion criteria for the systematic review while only four were selected for meta-analysis. The overall effects of standardized mean difference and 95% CI was -0.03 [95% CI -0.67 to 0.60] with a x2 statistic of 0.49 with 3 degrees of freedom (p>0.05), I2= 0.01%. Conclusion: CBCT is highly accurate and reproducible regarding linear measurements for assessing intrabony defects with a weighted standardized mean difference of 0.03 mm. More randomised controlled trials are required to assess the accuracy of CBCT in assessing patients with periodontal defects.